NON-FINANCIAL SUPPORT STRATEGIES FOR START-UP HOMESTAY ENTREPRENEURS: AN EXPLORATORY CASE STUDY OF A SMALL ISLAND RURAL AREA OF INDONESIA - Hiroshi Kuwahara, (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2020)
This study explores non-financial support strategies for start-up homestay entrepreneurs in rural communities on a small island in Indonesia from the perspective of international development agents (IDAs). Semi-structured interviews were conducted with start-up homestay entrepreneurs regarding their needs, expectations of support, and the challenges of starting a business. A focus group interview was conducted with tourism experts with knowledge of the research area, to garner opinion about non-financial support strategies. Data from these different interview types were qualitatively interpreted and compared in order to triangulate the findings and develop effective assistance strategies. Three suggestions arise from the research findings. First, support for entrepreneurs with experience of working in tourism-related businesses should be as specific as possible, following a preliminary consultation. Second, support for entrepreneurs with no experience of working in tourism-related businesses should include the provision of information about the key components of tourism, including tourists, hospitality, the tourism business, and homestays, with hands-on activities. Third, IDAs should develop a support system that includes family business-oriented entrepreneurs who have been relatively neglected by conventional support programs aimed at capacitybuilding in developing countries.